ANALYZING THE RELATIONSHIP BETWEEN PhET SIMULATION USE AND STUDENTS’ CONCEPTUAL UNDERSTANDING IN SCIENCE LEARNING - Winda Ismi; Ai Anisa Asaidah; Shinta Fitriani; Nana Nana (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2026)
The objective of this research is to analyze. the use of PhET Simulation in science learning and examine its relationship to their conceptual understanding. The research employed a quantitative approach with a descriptive correlational design. The study sample consisted of 30 students. Data were collected using a questionnaire on PhET Simulation usage and a test of students’ conceptual understanding. The questionnaire instrument was validated and deemed reliable prior to use. Data analysis was conducted using descriptive statistics, normality tests, and Spearman’s rho correlation tests with the aid of SPSS. The results indicated that the average score for PhET Simulation usage was 39.10 out of a maximum of 48, which falls into the high category. Meanwhile, the average score for students’ conceptual understanding was 70.33, with a relatively high variation among the students. The normality test results showed that one of the variables was not normally distributed; therefore, hypothesis testing was conducted using Spearman’s rho correlation. The Spearman’s rho correlation test yielded a coefficient of 0.082 with a significance level of 0.667 (p > 0.05), indicating that there was no significant relationship between PhET Simulation usage and students’ conceptual understanding. The findings suggest that PhET Simulation use has not become a dominant factor in improving students’ conceptual understanding, as it is still influenced by prior ability, learning motivation, and the instructional strategies employed by teachers.